HIV-1 prophylactic vaccines: state of the art - Jean-Daniel Lelièvre; Yves Lévy (Elsevier, 2016)
The quest for an effective HIV-1 vaccine began early in the course of the HIV pandemic. Over time, the paradigm has evolved from B cell- towards T cell-based vaccines. Results from initial Phase II/III trials have been disappointing; however, while modest, the unexpected results of the Phase II/III RV144 trial in Thailand have re-energised the field. Indeed a clear correlation was demonstrated in this trial between protection and immunological biomarkers, namely non-neutralising antibodies against the V1V2 region.Recent data obtained from cohorts of recently HIV-1-infected individuals have enabled exploration of the role of neutralising antibodies and their potential use in HIV-1 prevention. Results from non-human primate models using a cytomegalovirus vector have also shown the potential for a prophylactic HIV vaccine to induce effective T cell responses. Finally, the development of new vaccine vectors and trial strategies has also allowed progress in the field. Therefore, HIV-1 vaccine research remains a dynamic field that has also been stimulated by the recent positive results of pre-exposure prophylaxis strategies with antiretrovirals.